Association between small nucleolar RNA host gene expression and survival outcome of colorectal cancer patients: A meta-analysis based on PRISMA and bioinformatics analysis - Luo, Pei; Du, Jie; Li, Yinan; Ma, Jilong; Shi, Wenjun (Frontiers in Oncology, 2023)
Introduction Growing evidence shows that long non-coding RNA small nucleolar RNA host genes (lncRNA SNHGs) enact an pivotal regulatory roles in the shorter survival outcome of colorectal cancer (CRC). However, no research has systematically evaluated the correlation among lncRNA SNHGs expression and survival outcome of CRC. This research indented to screen whether exist potential prognostic effect of lncRNA SNHGs in CRC patientss using comprehensive review and meta-analysis. Methods Systematic searches were performed from the six relevant databases from inception to October 20, 2022. The quality of published papers was evaluated in details. We pooled the hazard ratios (HR) with 95% confidence interval (CI) through direct or indirect collection of effect sizes, and odds ratios (OR) with 95% CI by collecting effect sizes within articles. Detailed downstream signaling pathways of lncRNA SNHGs were summarized in detail Results 25 eligible publications including 2,342 patients were finally included to appraise the association of lncRNA SNHGs with prognosis of CRC. Elevated lncRNA SNHGs expression was revealed in colorectal tumor tissues. High lncSNHG expression means bad survival prognosis in CRC patients (HR=1.635, 95% CI: 1.405–1.864, P<0.001). Additionally, high lncRNA SNHGs expression was inclined to later TNM stage (OR=1.635, 95% CI: 1.405–1.864, P<0.001), distant lymph node invasion, distant organ metastasis, larger tumor diameter and poor pathological grade. Begg's funnel plot test using the Stata 12.0 software suggested that no significant heterogeneity was found. Conclusion Elevated lncRNA SNHGs expression was revealed to be positively correlated to discontented CRC clinical outcome and lncRNA SNHG may act as a potential clinical prognostic index for CRC patients.